2020
DOI: 10.12659/msm.922979
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 37 (IL-37) Reduces High Glucose-Induced Inflammation, Oxidative Stress, and Apoptosis of Podocytes by Inhibiting the STAT3–Cyclophilin A (CypA) Signaling Pathway

Abstract: Background Diabetic nephropathy (DN), the formation of albuminuria, is one of the most important complications seen in diabetic patients. IL-37, an inhibitor of congenital inflammation and immune response, plays an important role in the occurrence and development of diabetes, but its study in DN has not been previously reported. Material/Methods Podocyte transfection techniques were used to overexpress STAT3 and cyclophilin A (CypA). The expression of IL-37, STAT3, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
0
18
1
Order By: Relevance
“…5c ), indicating that CD147 is responsible for CyPA upregulation via JAK pathway. 30
Fig. 5 Spike protein-CD147-CyPA axis contributes to COVID-19 cytokine storm.
…”
Section: Resultsmentioning
confidence: 99%
“…5c ), indicating that CD147 is responsible for CyPA upregulation via JAK pathway. 30
Fig. 5 Spike protein-CD147-CyPA axis contributes to COVID-19 cytokine storm.
…”
Section: Resultsmentioning
confidence: 99%
“…4E). Previously, CyPA was reported to be regulated by the JAK-STAT pathway ( 24 ). Indeed, CyPA level could be inhibited by JAK inhibitor (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a positive correlation has been found between plasma eCyPA level and age, blood sugar level and hemoglobin A1c (HbA1c) level 46 . High glucose also activates signal transducer and activator of transcription 3 (STAT3)-CyPA interaction, which induces inflammation, oxidative stress, and apoptosis in podocytes 47 . IL-37 is an anti - inflammatory and anti - immune response molecule .…”
Section: Roles Of Cypa In Kidney Diseasesmentioning
confidence: 99%
“…IL-37 is an anti - inflammatory and anti - immune response molecule . A recent study has shown that overexpression of STAT3 and CyPA leads to inhibition of the IL - 37-mediated protective effects against podocyte injury induced by high glucose 47 . These data on kidney cells are consistent with those obtained from human umbilical endothelial cells demonstrating that STAT3 promotes CyPA expression via binding to the STAT3-responsive element (SRE), a specific region in the CyPA gene ( PPIA ) promoter 48 .…”
Section: Roles Of Cypa In Kidney Diseasesmentioning
confidence: 99%